2022
DOI: 10.3389/fpubh.2022.1055778
|View full text |Cite
|
Sign up to set email alerts
|

Association between nocturnal sleep duration and the risk of hyperuricemia among Chinese government employees: A cross-sectional study

Abstract: ObjectivesEvidence has shown that nocturnal sleep duration is associated with the risk of hyperuricemia, yet the findings are inconsistent. Thus, we aimed at exploring the association between nocturnal sleep duration and the risk of hyperuricemia in Chinese government employees.MethodsA total of 10,321 government employees aged 20–60 years were collected from the Cohort Study on Chronic Diseases among Government Employees in Hunan Province, China. Sleep duration was self-reported. And serum uric acid levels &a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
0
3
1
Order By: Relevance
“…Lee et al [41] found a U-shaped association between sleep duration and UA in Korean women, indicating that female individuals with a sleep duration of 7 to 8 hours showed the lowest UA level. In addition, many related studies have reported the negative association that increased sleep duration was significantly associated with a lower risk of HUA [42][43][44]. However, in this study, we found a threshold effect between sleep duration and HUA, indicating a positive association between HUA and sleep duration when sleep duration was <5 hours.…”
Section: Principal Findingscontrasting
confidence: 81%
“…Lee et al [41] found a U-shaped association between sleep duration and UA in Korean women, indicating that female individuals with a sleep duration of 7 to 8 hours showed the lowest UA level. In addition, many related studies have reported the negative association that increased sleep duration was significantly associated with a lower risk of HUA [42][43][44]. However, in this study, we found a threshold effect between sleep duration and HUA, indicating a positive association between HUA and sleep duration when sleep duration was <5 hours.…”
Section: Principal Findingscontrasting
confidence: 81%
“…Modifiable risk factors of HUA, such as excess body weight, dairy products, purine-rich food intake, alcohol consumption, sleep duration, etc . 6,15,19,20 have particular importance in disease prevention and control given their changeable levels and thereafter resulting in potential health benefits. Shi et al developed a prediction model of HUA that contains no invasive tests as predictors, in which BMI was selected as a modifiable risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…22 A study among Chinese government employees found that short nocturnal sleep duration was associated with a higher risk of HUA. 20 The mechanisms of the short sleep duration and HUA is still unclear. We hypothesized that the mediation effect between less sleep, obesity, elevated blood pressure and HUA can partially explain this association, but it still requires further verification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation